Profile of patients with post-tuberculosis bronchiectasis in a tertiary care hospital in Brazil - Vitor Loureiro Dias; Mariane Gonçalves Martynychen Canan; Cleverson Alex Leitão; Elissa Ayumi Okuno; Giulia Rafaela Dainez de Sant'Ana; Juan Vitor Miranda (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases, 2022)
Bronchiectasis are abnormal permanently dilated bronchi which lead to chronic cough and other respiratory symptoms. Though tuberculosis (TB) is a common cause of bronchiectasis, data on this association are scarce. The objective of this study was to describe the profile of patients with post-TB bronchiectasis at a tertiary hospital in the southern region of Brazil. This was a retrospective study with data from patients in follow-up at our hospital from January 2005 to December 2020. We included patients 14 years of age or older who had bronchiectasis on chest computed tomography and a history of pulmonary TB. We excluded patients with bronchiectasis due to other causes or with confirmed non-tuberculous mycobacteria infection. We included 54 of the 204 non-cystic fibrosis bronchiectasis patients seen at our hospital during the study period. Most of the patients were female, older, and non-smokers. Less than a third had chronic bronchial infection by some agent. More than two thirds had some type of ventilatory defect, the most common being obstruction. More than half had upper-lobe impairment. Severity of the disease seemed to be equally distributed from mild to severe. Treatment was varied, including bronchodilators, inhaled corticosteroids, and azithromycin. We found that the profile of patients in our hospital is similar to that described in other studies, with slight differences in regard to microbiology and treatment.